2020
DOI: 10.1016/j.lfs.2020.118601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into dimethyl cardamonin-mediated pharmacological effects: A double control of the AMPK-HMGB1 signaling axis

Abstract: Dimethyl cardamonin (DMC) has been isolated from diverse plants, notably from Cleistocalyx operculatus . We have reviewed the pharmacological properties of this natural product which displays anti-inflammatory, anti-hyperglycemic and anti-cancer properties. The pharmacological activities essentially derive from the capacity of DMC to interact with the protein targets HMGB1 and AMPK. Upon binding to HMGB1, DMC inhibits the nucleocytoplasmic transfer of the protein and its extracellular se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Acute kidney injury and chronic kidney disease are clinically intractable and complicated problems, and they are also interconnected in that AKI with unsatisfactory and delayed treatment could effortlessly progress to CKD, which dangerously ruins the patient’s life quality. , The morbidity and mortality of patients who suffer from AKI or CKD with intricate clinical syndromes remain high, and what is more urgent and worrying is that the therapeutic outcome of numerous drugs is limited due to their toxic side effects and renal sensitivity in patients with impaired renal function. , Encouragingly, natural products identified from dietary agents evidently displayed outstanding advantages in chemical novelty, moderate toxicity, metabolic absorption, and biological effects in recent decades. , Cardamonin (Alpinetin chalcone), occurring naturally in the fruit of the Alpinia species, has been validated tautologically to exhibit noticeable anti-inflammatory and antioxidant activities in inflammatory diseases, acute injuries, and various tumors. Nevertheless, the occurrence, progression, and pathogenesis of AKI and CKD differ from each other, whereas inflammation and oxidative stress are testified to be of vital importance in kidney diseases . Meanwhile, a certain number of targeted drugs by inflammation inhibition and oxidative restriction were tested in clinical trials to figure out their potential in clinical application. , In view of the necessity of obtaining therapeutic targets for kidney diseases induced by AKI or CKD and the excellent biological efficacy of CAD, we innovatively investigated the consequence of CAD treatment on I/R-caused AKI and UUO-generated renal fibrosis in animal and cellular models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute kidney injury and chronic kidney disease are clinically intractable and complicated problems, and they are also interconnected in that AKI with unsatisfactory and delayed treatment could effortlessly progress to CKD, which dangerously ruins the patient’s life quality. , The morbidity and mortality of patients who suffer from AKI or CKD with intricate clinical syndromes remain high, and what is more urgent and worrying is that the therapeutic outcome of numerous drugs is limited due to their toxic side effects and renal sensitivity in patients with impaired renal function. , Encouragingly, natural products identified from dietary agents evidently displayed outstanding advantages in chemical novelty, moderate toxicity, metabolic absorption, and biological effects in recent decades. , Cardamonin (Alpinetin chalcone), occurring naturally in the fruit of the Alpinia species, has been validated tautologically to exhibit noticeable anti-inflammatory and antioxidant activities in inflammatory diseases, acute injuries, and various tumors. Nevertheless, the occurrence, progression, and pathogenesis of AKI and CKD differ from each other, whereas inflammation and oxidative stress are testified to be of vital importance in kidney diseases . Meanwhile, a certain number of targeted drugs by inflammation inhibition and oxidative restriction were tested in clinical trials to figure out their potential in clinical application. , In view of the necessity of obtaining therapeutic targets for kidney diseases induced by AKI or CKD and the excellent biological efficacy of CAD, we innovatively investigated the consequence of CAD treatment on I/R-caused AKI and UUO-generated renal fibrosis in animal and cellular models.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its prominent inhibition properties in oxidative stress, tumorigenesis, inflammation, and infectious diseases, CAD is gradually revealing its potential to become a candidate strategy for therapeutics in related diseases. 13,14 For example, CAD protects against septic shock, osteoarthritis, and acute lung injury by obviously restraining the secretion of inflammatory cytokines and repressing inflammatory pathways. 15−17 Furthermore, the antioxidant pathways and capacities were enhanced after CAD treatment to successfully improve doxorubicin-generated cardiotoxicity, neurodegenerative disorders, and acute hepatic injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affecting the AMPK‐SIRT1‐PGC‐1α‐PPARs pathway can regulate lipid metabolism to alleviate obesity‐related diseases (Chen et al, 2019; Chyau et al, 2020; Diniz et al, 2021). Based on in vivo and in vitro studies, the stimulatory effects of DMC on glucose disposal and fatty acid oxidation, and the inhibitory effect on adipogenesis and inflammation, are primarily mediated by AMPK activation (Bailly & Vergoten, 2020; Choi et al, 2016). In this study, regular exercise slightly elevated AMPK expression.…”
Section: Discussionmentioning
confidence: 99%
“…The bud of Cleistocalyx operculatus is a traditional Chinese herb that has a long history of use in tonic drinks [ 21 ]. DMC (2',4'-dihydroxy-6'-methoxy-3',5'-dimethylchalcone) is a natural chalcone isolated from this bud that has shown pharmacological effects, such as anti-inflammatory, antihyperglycemic and anticancer activities [ 22 ]. Previously, starting with the scaffold of DMC, Yin et al designed a series of chalcone derivatives and found that the compound MY3 had the greatest ability to reverse DOX resistance in MCF-7 cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%